(untitled) (PerCursos, 2026)
This article examines peripheral insurgencies in Brazil through the interplay of marginal art, cultural resistance, and the activities of cultural collectives, with particular attention to the intersections of race, gender, and class. Employing a qualitative approach, the study is based on a literature review and a case study of Coletivo Nanda Produções, located in the municipality of Serra, Espírito Santo. The analysis focuses on the collective’s cultural practices and its role in the construction of collective memory within the local territory. Drawing on an interpretive framework, the article establishes a dialogue between artistic production during Brazil’s Military Dictatorship, particularly the work of Hélio Oiticica, and contemporary cultural expressions emerging from urban peripheries. It highlights the occupation of public space and collective organization as strategies for resisting multiple forms of oppression. The study explores how the collective promotes local knowledge, fosters memory-making processes, and strengthens community agency. The theoretical framework is informed by the works of Frantz Fanon, Kimberlé Crenshaw, and Marilena Chaui, among others. The analysis demonstrates how structural forms of oppression are challenged through artistic practices, positioning peripheral insurgency as an ongoing project of social justice, cultural democracy, and the recognition of diverse knowledge systems.